Pt nanoparticles embedded in CeO2 and CeZrO2 catalysts for biogas upgrading: Investigation on carbon removal mechanism by oxygen isotopic exchange and DRIFTS. Issue 49 (July 2021) - Marinho, André L.A.; Rabelo-Neto, Raimundo C.; Epron, Florence; Bion, Nicolas; Noronha, Fabio B.; Toniolo, Fabio Souza
Graphical abstract: Highlights: Pt embedded catalysts are highly stable in the dry reforming of methane reaction. The embedded structure promotes the oxygen mobility over support. The incorporation of Zr improves the oxygen mobility in the material. The embedded structure presents high oxygen lattice species responsible for coke gasification. Abstract: This work investigated the effect of Pt nanoparticles embedded into CeO2 (Pt@CeO2 ) and CeZrO2 (Pt@CeZrO2 ) on the carbon removal mechanism for the dry reforming of methane, in comparison to impregnated Pt/CeO2 . Morphological and structural characterization by TEM and Raman spectroscopy showed that Pt sintering is suppressed on both structures and the doping with Zr led to the CeZrO2 solid solution formation. A combination of TPR, oxygen isotopic exchange and DRIFTS measurements demonstrated that embedded Pt nanoparticles interact more strongly with ceria than supported Pt, and as a consequence, reactive lattice oxygen becomes more abundant on the catalyst surface, promoting the mechanism of carbon gasification over Pt nanoparticle. The low availability of oxygen species on Pt/CeO2 resulted in higher carbon formation, as demonstrated by TPO analysis. Therefore, the Pt@CeO2 and Pt@CeZrO2 catalysts were more resistant to coke formation due to the higher presence of reactive oxygen species at the metal-support interface, promoting the balance between the rates of carbon formation and carbon gasification over Pt nanoparticle.